Screening for dementia and associated factors in older adults from low socioeconomic communities in iLembe, KwaZulu-Natal - Xoli P. Mfene; Basil J. Pillay (AOSIS, 2024)
Background: Dementia is one of the leading non-communicable causes of disability and mortality in older adults, with recent research showing that it is increasing in low-middle-income countries compared to high-income countries. As such, multidisciplinary efforts are needed to effectively reduce the prevalence and risk of dementia through quick screening, diagnosis, and management of those with dementia and those at risk. Aim: The study's objectives were to estimate the prevalence of dementia and measure the sociodemographic and clinical risks in older adults in low socioeconomic communities. Setting: The study was conducted among older adults aged ≥ 60 years from the iLembe district in South Africa. Methods: This cross-sectional, one-phased, household study was conducted to screen for dementia over 8 months between October 2018 and October 2019. Demographic and clinical data were collected using a semi-structured questionnaire. In addition, the Mini-Mental Status Exam, Ascertain Dementia Eight-item questionnaire and Instrumental Activities of Daily Living Scale were administered to a multi-stage cluster sample of 320 participants to ascertain dementia prevalence. Frequencies and multivariate logistic regression were conducted to determine risk factors correlated with dementia. Results: The prevalence of dementia was 13.4%. Participants aged 80 years and above were 2.73 times more likely to develop dementia than participants younger than 80 years. Those with an education level of Grade 1-7 had a 69% less chance of developing dementia than those without formal education. Single participants showed an almost seven-fold increase in dementia. Lastly, depression increased the risk of dementia by two-fold. Conclusion: Dementia was probable in over one-sixth of the sample. Dementia risk factors were both modifiable and non-modifiable. Contribution: Dementia prevalence in South Africa is increasing and therefore it is crucial to develop a dementia plan that is specific to the South African context which will include strategies for early identification of the disease, reducing modifiable risks and strategic management of dementia associated medical conditions such as depression and vascular diseases.